Switching first contact: Photocontrol of E. coli adhesion to human cells - Möckl, Leonhard; Müller, A.; Bräuchle, C.; Lindhorst, T. K. (Chemical Communications, 2016)
We have shown previously that carbohydrate-specific bacterial adhesion to a non-physiological surface can be photocontrolled by reversible E/Z isomerisation using azobenzene-functionalised sugars. Here, this approach is applied to the surface of human cells. We show not only that bacterial adhesion to the azobenzene glycoside-modified cell surface is higher in the E than in the Z state, but add data about the specific modulation of the effect.
CRIS-Team Scopus Importer:2024-09-09